Kac-Moody construction of Toda type field theories - Aratyn, H.; Ferreira, L. A. [UNESP]; Gomes, J. F.; Zimerman, A. H. (Elsevier, 1991)
Using the coadjoint orbit method we derive a geometric WZWN action based on the extended two-loop Kac-Moody algebra. We show that under a hamiltonian reduction procedure, which respects conformal invariance, we obtain a hierarchy of Toda type field theories, which contain as submodels the Toda molecule and periodic Toda lattice theories. We also discuss the classical r-matrix and integrability properties.